A Novel Impregnation-Reduction Method Combined with Galvanic Replacement for Fabricating Low Cost MEA with High Performance for PEM Fuel Cells. Issue 3 (30th March 2021) - Chen, Zhenjie; Fu, Tao; Kong, Xiangbang; Chen, Xingqiao; Yang, Qi; Zhao, Jinbao; Li, Bing; Luo, Jiangshui
Abstract : The fuel cells have outstanding advantages in the new energy application, but the membrane electrode assembly (MEA) of fuel cells is difficult to produce at low-cost and large-scale, which restricts their applications. To simplify the preparation of MEA, for the first time, we successfully develop a novel impregnation-reduction method combined with galvanic replacement to grow Ag/Pt bimetallic nanocatalyst onto a Nafion membrane (Nafion-Ag/Pt membrane), and the deposited Ag/Pt catalyst is very stable, which can be directly used as a novel ultra-thin catalyst layer in MEA. This novel method possesses mild conditions, simple procedure, good repeatability and practicability in a large-scale production. Moreover, a very low Pt loading amount of Nafion-Ag/Pt membrane can be achieved by regulating experimental conditions, which brings excellent Pt utilization. Therefore, the MEA made from Nafion-Ag/Pt membrane exhibits a Pt mass specific power (1.519 W mgPt −1 ) that is 12.3 times higher than that of a conventional MEA. These results demonstrate that this novel impregnation-reduction method can reduce the cost of fuel cells by reducing the difficulty of MEA preparation and the Pt loading amount of MEA and simultaneously enhancing its performance, which shows great potential in fuel cell application.